2005
DOI: 10.1128/jvi.79.18.11824-11836.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ubiquitination and Stabilization of Human Ubiquitin E3 Ligase PIRH2 by Measles Virus Phosphoprotein

Abstract: Using a C-terminal domain (PCT) of the measles virus (MV) phosphoprotein (P protein) as bait in a yeast two-hybrid screen, a cDNA identical to the recently described human p53-induced-RING-H2 (hPIRH2) cDNA was isolated. A glutathione S-transferase-hPIRH2 fusion protein expressed in bacteria was able to pull down P protein when mixed with an extract from P-expressing HeLa cells in vitro, and myc-tagged hPIRH2 could be reciprocally coimmunoprecipitated with MV P protein from human cells. Additionally, immunoprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 51 publications
1
43
0
Order By: Relevance
“…These motifs are located in different positions in various P proteins, e.g., in the P protein of the family Paramyxoviridae, the coiled-coil motifs are mostly located in the C terminus (1,10,11,12,30,37,43,48,49), whereas the coiled-coil motif in respiratory syncytial virus is situated in the central part of the P protein (8) and the putative coiled-coil motif of Marburg virus and Ebola virus VP35 (family Filoviridae) is located at the N terminus which was shown to be essential for self-association (35). It is interesting that the VSV Pind also contains a predominant coiledcoil motif (12,27), which is located at the amino-terminal region as predicted by COILS prediction software (33); the region spans residues 16 to 36 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These motifs are located in different positions in various P proteins, e.g., in the P protein of the family Paramyxoviridae, the coiled-coil motifs are mostly located in the C terminus (1,10,11,12,30,37,43,48,49), whereas the coiled-coil motif in respiratory syncytial virus is situated in the central part of the P protein (8) and the putative coiled-coil motif of Marburg virus and Ebola virus VP35 (family Filoviridae) is located at the N terminus which was shown to be essential for self-association (35). It is interesting that the VSV Pind also contains a predominant coiledcoil motif (12,27), which is located at the amino-terminal region as predicted by COILS prediction software (33); the region spans residues 16 to 36 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…HeLa cells in six-well plates were infected with vTF7-3 for 1 h at a multiplicity of infection of 10, washed, and then transfected with the appropriate plasmids in the presence of Lipofectamine 2000 (Invitrogen). After 24 h of transfection, cell lysates were prepared as described elsewhere (10). In experiments to map the self-association domain of Pind protein, Myc-tagged Pind was coexpressed with HA-tagged Pind or mutants in various combinations.…”
Section: Cells and Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental Vero, si1 and si2 cells were infected at indicated MOI with recombinant viruses with or without addition of 10 g/ml of fusion inhibitor peptide z-fFG to prevent syncytium formation. Viral protein expression was determined by flow cytometry analysis of cells labeled with the Y503 anti-F monoclonal antibody and/or GFP detection, detection of the expression of viral N (cl25 antibody), P (49.21 antibody), HA-P 2 (anti-HA antibody; Sigma), Flag-P 1 (anti-Flag antibody; Sigma), and cellular GAPDH (MAb374 antibody; Chemicon) protein by Western blotting revealed by chemiluminescence as detailed previously (22,23). Unexpectedly, when the P protein was tagged with the HA peptide, its recognition by 49.21 monoclonal antibody anti-P was reduced.…”
Section: Methodsmentioning
confidence: 99%
“…phosphoprotein (3), N-terminal kinase-like proteinbinding protein 1 (NTKL-BP1) (22), and calmodulin (5). Recently, it has been reported that histone deacetylase 1 (HDAC1) and the ε-subunit of coatomer complex (ε-COP) were ubiquitylated and subsequently degraded by Pirh2 (13,14).…”
Section: Mammalian Expression Vectors and Transfectionmentioning
confidence: 99%